2006
DOI: 10.1200/jco.2006.06.7595
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II and Translational Study of Cetuximab in Metastatic Colorectal Carcinoma Refractory to Irinotecan, Oxaliplatin, and Fluoropyrimidines

Abstract: Cetuximab is active and well tolerated in metastatic CRC refractory to irinotecan, oxaliplatin, and fluoropyrimidines. The severity of rash was related to efficacy. Neither EGFR kinase domain mutations nor EGFR gene amplification appear to be essential for response to cetuximab in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
256
3
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 481 publications
(283 citation statements)
references
References 47 publications
20
256
3
4
Order By: Relevance
“…In BOND I, patients treated with CxIri and developing severe skin rash, RR was 55%, TTP was 8.2 months and median OS was 13.7 months, respectively, and the degree of rash as a predictive marker for RR and OS has been confirmed in many studies (Lenz et al, 2006;Pfeiffer et al, 2007b).…”
Section: Predicting Efficacy Of CX and Pamentioning
confidence: 83%
See 1 more Smart Citation
“…In BOND I, patients treated with CxIri and developing severe skin rash, RR was 55%, TTP was 8.2 months and median OS was 13.7 months, respectively, and the degree of rash as a predictive marker for RR and OS has been confirmed in many studies (Lenz et al, 2006;Pfeiffer et al, 2007b).…”
Section: Predicting Efficacy Of CX and Pamentioning
confidence: 83%
“…Comparison of Cx and Pa RR for Cx and Pa single agents (8-11%) are very similar in pretreated patients Malik et al, 2005;Lenz et al, 2006;Peeters et al, 2006). There was no improvement in median OS, neither in the Peeters study nor in the BOND I study, but this lack of difference may be caused by the fact that many patients in both studies received salvage therapy upon PD.…”
Section: Role Of Antibody Therapy P Pfeiffer Et Almentioning
confidence: 96%
“…In fact, amplification was found in three patients only. Furthermore, Lenz et al (2006) reported that EGFR amplification is not related to response to cetuximab, questioning the role of EGFR amplification in the prediction of clinical activity of EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab, a monoclonal antibody, has been demonstrated to produce a 10% response rate in monotherapy and a 20% when combined with irinotecan even in patients refractory to this drug (Cunningham et al, 2004;Lenz et al, 2006). …”
mentioning
confidence: 99%
“…While studies have shown an added benefit for patients receiving cetuximabþirinotecan-based therapy compared to patients receiving cetuximab monotherapy, irinotecan-intolerant patients are likely to receive cetuximab alone. 6,9,19,20 Therefore, we also modeled a cetuximab-only strategy in which patients received 400 mg/m 2 of cetuximab during the first week of therapy and 250 mg/m 2 every week thereafter. Finally, we included a panitumumab-only strategy in which patients received 6 mg/kg of panitumumab every 2 weeks.…”
Section: Chemotherapy Regimensmentioning
confidence: 99%